Marketing Strategy Analysis Using WhatsApp Social Media - Badik, Muhammad; Gerhani, Febrina; Redjeki, Sri (Golden Ratio of Marketing and Applied Psychology of Business, 2025)
This study aims to determine and identify marketing strategies using WhatsApp social media in selling Sevina Shop SME products and the effectiveness of using WhatsApp as a product marketing medium. This research uses a descriptive qualitative approach with data collection methods through observation, interviews, and documentation. Data analysis uses Miles and Huberman's data analysis, including data reduction, presentation, and conclusion drawing/verification. Data analysis is carried out by identifying patterns and central themes that describe the application of marketing strategies in using WhatsApp social media, and drawing conclusions based on the findings that have been analyzed. The results of this study show that applying marketing strategies using WhatsApp social media is very practical in helping the Sevina Shop SME find market opportunities, determine strategies in achieving target markets, identify market needs, determine product positions, foster consumer interest, and increase sales. The results of this study are expected to provide in-depth insight into the application of marketing strategies using WhatsApp social media in product sales. They can help SME develop effective marketing strategies to increase their business competitiveness.